An "urban voluntary association" in the rural South? Urbanity, race, and the United Daughters of the Confederacy, 1910–1930. (20th October 2022) - Chamberlain, Adam; Yanus, Alixandra B.
ABSTRACT: Historians describe the United Daughters of the Confederacy (UDC) as an urban movement, but the reasons for its urban focus have not been adequately explored. This is intriguing because the UDC was most vibrant during the first three decades of the twentieth century, when white and black citizens alike were leaving rural southern communities for urban centers – and as white politicians increasingly enforced Jim Crow restrictions. In this study, we examine the effects of urbanity and race on local UDC chapters and membership across the South. We find that although UDC chapters were not overwhelmingly urban, members largely joined urban chapters – particularly those located in smaller cities. Chapters and members were also more common in cities with larger black populations, suggestive of a racial contact stimulus. These findings lead us to question the UDC's relationship to the predominately rural South as well as its ability to broadly represent southern white women. They also speak to other research on voluntary associations during this period, underscoring that southern urbanity inspired civil society, albeit based on separation rather than integration.